ChemInform Abstract: Cytotoxic Triterpene Saponins from Cercodemas anceps. Issue 45 (November 2015) - Cuong, Nguyen Xuan; Vien, Le Thi; Hanh, Tran Thi Hong; Thao, Nguyen Phuong; Thao, Do Thi; Thanh, Nguyen Van; Nam, Nguyen Hoai; Thung, Do Cong; Kiem, Phan Van; Minh, Chau Van
Abstract isolation and structure of five new holostane‐type triterpene saponins, cercodemasoides A—E (structures of cercodemasoides D (Ia) and E (Ib) are shown)